Pengaruh Pemberian Jus Buah Belimbing Wuluh (Averrhoa bilimbi L.) terhadap Kadar Kolesterol LDL Darah Tikus Putih (Rattus norvegicus) Jantan Galur Wistar dengan Diet Tinggi Lemak - Rahminiwati, Kartika Dwi; Hambarsika, IGM Antara; Handajani, Fitri (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2019)
A high-fat diet can increase lipoprotein levels, total cholesterol, (Low Density Lipoprotein) LDL, and triglycerides. Starfruit has saponin and flavonoid compounds which are expected to reducing LDL cholesterol levels. The aim of the study was to determine the effect of starfruit juice on lowering the blood cholesterol LDL of Wistar rats fed with high-fat diet. Experimental study with post-test only control group design. As many as 24 male white rats from the Wistar strain were divided into 3 groups: negative control groups (K-) that were given standard feed for 28 days; positive control group (K+) who were given a high-fat diet for 28 days; the treatment group (KP) was given a high-fat diet for 28 days and on the 15th day 28th they were given a starfruit juice with a dose of 4ml / 200grBB / day. Day 29 measured LDL cholesterol. The statistic test showed a significant increase in LDL cholesterol levels (p=0.001) in the positive control group (x=12.125±2.642 mg/dL) compared to the negative control group (x=7.625±1.506 mg/dL). There was no significant different the mean cholesterol level of the treatment group (x=11±1.927) compared to the mean LDL cholesterol level of the positive control group (x=12.125±2.642). A high-fat diet significantly increases the mean LDL cholesterol level. Starfruit juice did not significantly reduce LDL cholesterol level.